Pelatihan Manajemen Pemasaran Berbasis Website pada Usaha Kue Wecakee Denpasar - Ni Putu Nanik Hendayanti; Kadek Dwi Pradnyani Novianti; Luh Putu Safitri Pratiwi (LPPM Universitas Bumigora, 2021)
The development of the home industry, especially in Bali, is currently a very promising business for the perpetrators. Business growth in Bali reaches 4% per year. Wecakee Denpasar is one of the home industries engaged in cake making. This cake-making business only has a homestore and is run by the owner, I Ketut Gede Andrayuga. Wecakee Denpasar produces various kinds of cakes such as cakes, pastries, and sponge. So far, the marketing system carried out by Wecakee Denpasar is word of mouth and is usually based on the friend's relationship with the owner. Seeing the condition of marketing management like this, it causes an uncertain amount of production every day. Based on the description above, the priority problem experienced by partners is marketing management which is still done conventionally, therefore the objectives of this community service activity at Wecakee Denpasar are: Creating a Wecakee Denpasar marketing website. The results of this service, namely the evaluation using a questionnaire, obtained the results of the Very Good index category with an index value of 92.5%.